Overview: Distribution, Occurrence, and Origins of Methane Hydrates around the Japan Islands - Matsumoto, Ryo; Hiruta, Akihiro; Oi, Takeshi; Kakizaki, Yoshihiro; Shimono, Takaya; Ishida, Naoto; Saeidi-ortakand, Mahsa; Snyder, Glen; Tomaru, Hitoshi; Fukuda, Akari; Hiromatsu, Mineo; Ohkawa, Shiro; et al. (Journal of Geography (Chigaku Zasshi), 2024)
Due to the current energy crisis caused by global warming and geopolitical events, evaluating the energy potential of marine gas hydrates around the Japan Islands has become an urgent issue. Based on open and public reports, a critical overview is provided of the current status of the exploration of gas hydrates in the eastern Nankai Trough and along the eastern margin of the Japan Sea. In 2001, an exploration and resource assessment of gas hydrates in the eastern Nankai Trough was launched as a national project. In the late 20th century, hydrate-induced BSRs had been widely recognized on the fore-arc basins and slopes of the accretionary wedges of the Nankai Trough. Integrated geological and geophysical exploration reveals that the hydrates of the eastern Nankai Trough occur in the interstitial pore space of sand layers (pore filling type) of the Early Pleistocene turbidite units of 100 to 200 m in thickness above the BSR-BGHS. Hydrate exploration in the Japan Sea entered the National project in 2012, following academic efforts over the preceding 10 years, confirming 1,742 columnar-shaped gas chimney structures (generally a few hundred meters across and roughly 100 m deep) in which a few centimeters to nearly 50 m of thick massive hydrate deposits occur in the Middle Pleistocene silty host sediments. Japan Sea hydrates are considered to have grown in the host sediments, displacing clayey particles (particle displacement type). Gas chimney structures are the main conduits for the migration of deep-seated methane, associated with sea floor methane seeps, chemosynthetic communities, and methane-derived authigenic carbonates. A high concentration of massive hydrate is related to enhanced maturation and accumulation of hydrocarbon deposits under the high heat flow of the Japan Sea basin. Additionally, glacial eustasy of the closed Japan Sea basin facilitated efficient recycling of methane to accumulate massive hydrates.